Cigarette Butts as Water Emerging Contaminants: Possible Method for Their Remediation - Ajibade, Sinazo; Nnadozie, Ebenezer C.; Gulyás, Miklós; Simon, Barbara (Journal of Central European Green Innovation, 2023)
Nano-sized particles derived from cigarette butts (CBs) are extremely small particles, typically less than 100 nanometers in size, generated by the degradation or breakdown of CB materials. The potential impact of nano-sized particles derived from CBs on irrigation water is a topic of concern. Despite the lack of research focusing specifically on these aspects, it is essential to consider the potential risks associated with these particles. The presence of toxic compounds in CBs, such as nicotine, heavy metals, and polycyclic aromatic hydrocarbons (PAHs), raises concerns about the potential health risks of consuming water contaminated with nano-sized particles from CBs and the potential for these particles to accumulate in the soil, affecting nutrient availability and overall crop growth. Nano-sized particles can travel through water systems and may reach irrigation channels and sources through various pathways, and if CB nano-litter is present in nearby surface water bodies or infiltrates into groundwater, it can introduce these particles and associated contaminants into water sources and the agricultural environment. To ensure the safety and limited entry into water sources used for irrigation it is crucial to implement effective water treatment processes capable of removing or reducing nano-sized particles, as well as the associated chemicals, from the water supply. To mitigate potential risks, various water purification methods can be considered, such as the use of magnetic biochar. Magnetic biochar is a type of biochar that is enriched with magnetic materials. It has been explored as a potential tool for wastewater treatment due to its ability to attract and adsorb contaminants. The hybridized properties of both organic and inorganic materials in magnetic biochar promote its adsorptive ability for a wide range of contaminants. Also, it has unique properties such as solar responsiveness, reusability, magnetic recovery, magnetic recovery, and surface functionalization which are desirable in the design of recyclable adsorbent for industrial wastewater treatment. Therefore, by incorporating magnetic biochar in water treatment systems, it may be possible to effectively remove nano-sized particles derived from CBs, along with other pollutants and contaminants, from water. For example, metal ions can be adsorbed via ligand exchange and complexation, while nicotine and PAHs are primarily via π-π interaction, hydrogen bonding, and electrostatic interactions. Therefore, the present study will assess the potential capacity of magnetic biochar to adsorb these particles, considering its impact on water remediation, soil health, and crop growth, and evaluate the overall cost-effectiveness and practicality of its implementation.